Perception of lip aesthetics of repaired cleft lip among professionals, laypersons and cleft patients using three-dimensional images / Low Mabel - Low, Mabel (2019)
Introduction: Specialized treatment is necessary for cleft lip and palate patients from their early periods of life until adulthood. Often, the scars formed in the lip region are left behind. These impaired appearances can affect patients’ psychosocial well-being and ultimately, their quality of life. A difference in aesthetic perception may exist among individuals with different professional backgrounds. The observed differences may be related to the level of knowledge, perception and exposure between the groups. There is more emphasis now on patients’ own views or perception on what they want to achieve at the end of their treatment. This research can therefore help clinicians to better understand cleft patients’ needs and expectations so that treatment provided in future can be improved upon. Objectives of study: To determine the differences in perception on lip aesthetics by dental professionals, laypersons and cleft patients, and to investigate the influence of lip asymmetry on aesthetic perception. Materials and method: Three-dimensional images of treated cleft lips and of controls were presented in random order to three groups of raters, i.e. cleft patients, dental professionals and laypersons. For each image, the raters had to evaluate the lip attractiveness using Visual Analog Scale (VAS), ranging from 0-10cm. Differences in mean VAS scores given by the observer groups were analyzed using one-way analysis of variance (ANOVA). Pearson correlation coefficient was used to investigate the relationship between lip asymmetry and aesthetic scores. iv Results: The mean VAS score for the treated cleft images was 3.6 lower than that of non-cleft images (5.2 vs 8.8) and this difference was statistically significant. There was no significant difference in the VAS scoring by the three rater groups. Although not significant, a negative correlation was found between the amount of lip asymmetry and VAS score. Conclusion: Treated cleft lips had significantly lower aesthetic scores than normal lips. The professional background of raters did not influence their perception of lip aesthetics. The level of asymmetry also did not affect their aesthetic scoring